The Exclusion of Immigrants from Welfare Programs : Cross-National Analysis and Contemporary Developments - Koning, Edward Anthony, 1982- (Book collections on Project MUSE., 2022)
"In light of the increase in cross-border mobility and the recent political sensitivity surrounding immigration-related issues, understanding the politics and policies of immigrants' access to welfare programs is more relevant than ever. Systematic analysis of this subject has been held back, however, by the lack of a cross-national index of immigrant exclusion from social benefits over time. The Exclusion of Immigrants from Welfare Programs fills this gap by taking advantage of a novel and original measure called the Immigrant Exclusion from Social Programs Index (IESPI), which includes twenty-five indicators regarding immigrants' access to seven different social programs, for twenty-two countries, at four moments in time. The book includes an assessment of key trends, an investigation of the origins and consequences of variation, and detailed studies of four cases of particular theoretical interest: Norway, Austria, Portugal, and the United States. Presenting a cross-national index to facilitate and encourage systematic cross-country comparisons, this book provides insights and data that will allow researchers to probe such questions as the degree to which countries include or exclude immigrants in developing public policies, why some countries are more exclusionary than others, and what the future consequences of this exclusion might be."--